A new approach to producing transparent ZnAl2O4 ceramics. Issue 7 (July 2017) - Belyaev, A.V.; Evdokimov, I.I.; Drobotenko, V.V.; Sorokin, A.A.
Abstract: A new approach to producing of transparent bulk ZnAl2 O4 ceramics based on hot pressing of powders (1600 °С, 50 МPа) in presence of sintering additive ZnF2 is described. Using this approach in the presence of 5 wt% of ZnF2 transparent ZnAl2 O4 ceramics was prepared with transparency range from 0.2 to 7.5 μm and with band gap of about 6.05 eV. The average grain size was about 33 μm and the transmittance at the wavelength of 550 nm was about 63%.